PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK PADA POKOK PEMBAHASAN SEGITIGA DI KELAS VII SMP NEGERI 1 TOMBATU - Oroh, Therezia Imelda; Pesik, Anekke; Tumalun, Nicky K. (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
The purpose of this study was to examine the effect of the implementation of the Pair Check model on student learning outcomes in the Triangle material. This research is a research that uses Posttest-Only Control Group Design. The subjects in this study were class VII B as an experimental class consisting of 20 students and class VII C as a control class consisting of 20 students at SMP Negeri Tombatu in the academic year 2021/2022 who were randomly selected. The data obtained are posttest results in the experimental class and control class, with the average learning outcomes in the experimental class =77.35 and the average learning outcomes in the control class =48.2. Testing the data after using the significance level = 0.05 obtained = 7.48029 = 1.68595 and concluded is rejected. The conclusion of this study is the average learning outcomes of students who learn to use the Pair Check model on the triangle meter is higher than the learning outcomes of students who learn to use the Direct Instruction learning model.Keywords: Pair Check, learning outcomes, triangle